2023
DOI: 10.5713/ab.22.0124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolites in rumen fluid, urine, and feces of dairy cow from subacute ruminal acidosis model measured by proton nuclear magnetic resonance spectroscopy

Abstract: Objective: In this study, metabolites that changed in the rumen fluid, urine and feces of dairy cows that were fed different feed ratios were investigated. Methods:Eight Holstein cows were used in this study. Rumen fluid, urine, and feces were collected from the normal concentrate diet (NCD) (Italian ryegrass 80%: concentrate 20% in the total feed) and high concentrate diet (HCD) groups (20%: 80%) of dairy cows. Metabolite analysis was performed using proton nuclear magnetic resonance (NMR) identification, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Delineating the consequences of the feed ratio on the metabolite production in dairy cows may provide critical information for understanding the factors impacting milk yield. Our previous study reported metabolite changes in rumen fluid, urine, and feces induced by subacute ruminal acidosis due to a highly concentrated diet [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delineating the consequences of the feed ratio on the metabolite production in dairy cows may provide critical information for understanding the factors impacting milk yield. Our previous study reported metabolite changes in rumen fluid, urine, and feces induced by subacute ruminal acidosis due to a highly concentrated diet [ 13 ].…”
Section: Discussionmentioning
confidence: 99%